Nano Wave Plates Structuring and Index Matching in Transparent Hydroxyapatite-YAG Ce Composite Ceramics for High Luminous Efficiency White Light-Emitting Diodes - Huang, Ping (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.